Identification and expression analysis of calcium-dependent protein kinase family in oat (Avena sativa L.) and their functions in response to saline-alkali stresses - Li, Ya-nan; Lei, Chunyan; Yang, Qian; Yu, Xiao; Li, Siming; Sun, Yan; Ji, Chunli; Zhang, Chunhui; Xue, Jin-ai; Cui, Hongli; Li, Runzhi (Frontiers in Plant Science, 2024)
Calcium-dependent protein kinases (CDPKs) serve as calcium ion sensors and play crucial roles in all aspects of plant life cycle. While CDPK gene family has been extensively studied in various plants, there is limited information available for CDPK members in oat, an important cereal crop worldwide. Totally, 60 AsCDPK genes were identified in oat genome and were classified into four subfamilies based on their phylogenetic relationship. The members within each subfamily shared similar gene structure and conserved motifs. Collinearity analysis revealed that AsCDPK gene amplification was attributed to segmental duplication events and underwent strong purifying selection. AsCDPK promoters were predicted to contain cis-acting elements associated with hormones, biotic and abiotic stresses. AsCDPK gene expressions were induced by different salt stresses, exhibiting stress-specific under different salt treatments. Moreover, overexpression of AsCDPK26 gene enhanced salt resistance in C. reinhardtii, a single-cell photoautotrophic model plants. Further analysis revealed a significant correlation between AsCDPK26 and Na + /H + antiporter 1 (p<0.05), suggesting that AsCDPK26 may interact with ion transporter to modulate salt resistance. These results not only provide valuable insights into AsCDPK genes in response to different salt stresses, but also lay the foundation to mine novel candidates for improving salt tolerance in oat and other crops.